The philosophy of money - Simmel, Georg, 1858-1918.; Frisby, David (London ; New York : Routledge, 2004)
This title provides wide-ranging discussions of the social, psychological and philosophical aspects of the money economy, giving insights into the forms that social relationships take. It analyses the relationships of money to exchange, the human personality, the position of women, and individual freedom.
Chapter Introduction to the Translation -- chapter The Philosophy of Money -- part Analytical Part -- chapter 1 Value and Money -- chapter 2 The Value of Money as a Substance -- chapter 3 Money in the Sequence of Purposes -- part Synthetic Part -- chapter 4 Individual Freedom -- chapter 5 The Money Equivalent of Personal Values -- chapter 6 The Style of Life.
"First published in 1978 by Routledge and Kegan Paul Ltd."--Title page verso
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Money; Liberty; Freedom; Liberté.; freedom; BUSINESS & ECONOMICS -- Money & Monetary Policy; Money; Geld